Cadmium selenide by XPS - Ospina, Rogelio; Rincon-Ortiz, Sergio A; Rodriguez Pereira, Jhonatan (American Institute of Physics, 2020)
Cadmium selenide was analyzed using x-ray photoelectron spectroscopy. The specimen is a powder purchased from Chemsavers. The sample was fixed to a stainless-steel sample holder with copper 3M (TM) double-sided adhesive tape. Survey spectra, Cd 3d, Se 3d, O 1s, Cd 3p, Cd MNN, Se LMM, Se 3p, C 1s, and Cd 4d core level along with the valence band spectra were recorded. Results point out a stoichiometry of 0.95 on surface.
Selenid kadmia pomocí XPS
Keywords: CdSe; XPS; metal chalcogenide; semiconductor; CdSe; metal dichalcogenides; XPS; polovodič